Strength-limiting damage in lithium silicate glass-ceramics associated with CAD–CAM. Issue 1 (January 2019) - Romanyk, Dan L.; Martinez, Ysidora Torrealba; Veldhuis, Sydney; Rae, Nyssa; Guo, Yilan; Sirovica, Slobodan; Fleming, Garry J.P.; Addison, Owen
Abstract: Objective: The fabrication of all-ceramic restorations using Computer Aided Design and Computer Aided Manufacturing (CAD–CAM) most commonly involves subtractive machining which results in strength-limiting, surface and sub-surface damage in the resultant prosthesis. The objective was to explore how clinically relevant machining-process variables, and material variables, affect damage accumulation in lithium silicate glass-ceramics. Methods: Three commercial lithium silicate glass-ceramics (IPS e.max® CAD, Celtra® Duo and Vita Suprinity®) were selected. For each material, two groups of disk-shaped specimens were fabricated (n = 15), using a CAD–CAM process, creating surfaces equivalent to those generated for a dental restoration, or alternatively, using a highly controlled laboratory process generating disk-shaped test specimens with a consistent polished surface. Bi-axial flexure strength (BFS) was determined in a ball-on-ring configuration and fractographic analyses performed. For each material BFS was correlated with machining sequence and with surface roughness. Results: BFS was significantly influenced by material substrate (p < 0.01) and by fabrication route (p < 0.01). A significant factorial interaction (p < 0.01) identified that the magnitude of changes in BFS when comparing the two specimen fabrication routes, was dependent on substrate type. The polished control specimens exhibited a significantly increased BFS when compared with the CAD–CAM counterparts for all materials. IPS e.max® CAD and Celtra® Duo showed a 44 and 46% reduction in mean BFS for the CAD–CAM specimens when compared with the polished counterparts, respectively. In contrast, Vita Suprinity® showed the least disparity in mean BFS (21%) but the greatest variance in BFS data. Significance: All CAD–CAM specimens showed evidence of machining introduced damage in the form of median and radial cracks at sites either coincident with, or peripheral to the failure origin. Subtractive machining introduced significant strength limiting damage that is not eliminated by heat treatments applied for either microstructure development (IPS e.max® CAD and Vita Suprinity®) or annealing/crack blunting (Celtra® Duo).